Hot-melt extrusion : pharmaceutical applications - Douroumis, Dennis (Chichester, West Sussex, UK : Wiley, 2012)
"Hot-melt extrusion (HME) - melting a substance and forcing it through an orifice under controlled conditions to form a new material - is an emerging processing technology in the pharmaceutical industry for the preparation of various dosage forms and drug delivery systems, for example granules and sustained release tablets. Hot-Melt Extrusion: Pharmaceutical Applications covers the main instrumentation, operation principles and theoretical background of HME. It then focuses on HME drug delivery systems, dosage forms and clinical studies (including pharmacokinetics and bioavailability) of HME products. Finally, the book includes some recent and novel HME applications, scale -up considerations and regulatory issues. Topics covered include: principles and die design of single screw extrusion twin screw extrusion techniques and practices in the laboratory and on production scale HME developments for the pharmaceutical industry solubility parameters for prediction of drug/polymer miscibility in HME formulations the influence of plasticizers in HME applications of polymethacrylate polymers in HME HME of ethylcellulose, hypromellose, and polyethylene oxide bioadhesion properties of polymeric films produced by HME taste masking using HME clinical studies, bioavailability and pharmacokinetics of HME products injection moulding and HME processing for pharmaceutical materials laminar dispersive & distributive mixing with dissolution and applications to HME technological considerations related to scale-up of HME processes devices and implant systems by HME an FDA perspective on HME product and process understanding improved process understanding and control of an HME process with near-infrared spectroscopy Hot-Melt Extrusion: Pharmaceutical Applications is an essential multidisciplinary guide to the emerging pharmaceutical uses of this processing technology for researchers in academia and industry working in drug formulation and delivery, pharmaceutical engineering and processing, and polymers and materials science"--
"First book related to the use of hot melt extrusion for pharmaceutical applications"--
Hot-melt Extrusion:Pharmaceutical Applications; Contents; List of Contributors; Preface; 1. Single-screw Extrusion: Principles; 1.1 Introduction; 1.2 Ideal Compounding; 1.3 Basics of the Single-screw Extruder; 1.3.1 Screw Feed Section; 1.3.2 Screw Compressor Section; 1.3.3 Screw Metering Section; 1.3.4 Mixers; 1.3.5 Limitations of Conventional Single-screw Mixers; 1.4 SSE Elongational Mixers; 1.5 Summary; References; 2. Twin-screw Extruders for Pharmaceutical Hot-melt Extrusion: Technology, Techniques and Practices; 2.1 Introduction; 2.2 Extruder Types and Working Principle.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Molding (Chemical technology); Drugs -- Extrusion; Pharmaceutical chemistry; Drug delivery systems; SCIENCE -- Chemistry -- Organic; Electronic books; Electronic books